Characterization and phylogenetic analyses of the complete mitochondrial genome of Sillaginopsis panijus (Perciformes: Sillaginidae). Issue 11 (2nd November 2021) - Saha, Shilpi; Song, Na; Baki, Mohammad Abdul; Yang, Tianyan; Gao, Tianxiang
Abstract: The complete mitochondrial genome of Sillaginopsis panijus has been determined for the first time using Sanger Dideoxy DNA sequencing. The mitogenome is a circular molecule of 16, 529 bp in length. It contains 37 mitochondrial genes (13 protein-coding genes, two ribosomal RNA, and 22 transfer RNA) and a control region as other bony fishes. In the phylogenetic analysis using 12H-strand protein-coding genes, monotypic S . panijus is situated separately from the genus Sillago . The present phylogeny supports its taxonomic position according to morphology and will be helpful for evolutionary analysis.